Insights for Indigenous Policy from the Applied Behavioural Sciences. Issue 1 (7th November 2016) - Biddle, Nicholas
Abstract: People are neither completely rational, nor completely random in their decisions. Rather, they exhibit predictable biases that not only make it less likely that they will achieve their own stated desires, but also complicate the design and efficiency of public policy. These are some of the insights of the emerging applied behavioural sciences. With some notable exceptions, these insights have not always filtered through to policy formulation. Policy related to Aboriginal and Torres Strait Islander (Indigenous) Australians is one example of an area where insights from the applied behavioural sciences have the potential to improve the quality of policy decisions. A large amount of government funds is spent on Indigenous people reflecting a high degree of disadvantage. This paper provides new data and insights to understand the patterns and factors associated with decisions made by Indigenous people, thereby helping to improve the effectiveness of Indigenous policy.